MORPHOLOGICAL CHANGES IN COPPER SULFATE POISONING - A CASE OF SUICIDE - Atanas Hristov; Teodora Kiryakova; Alexandаr Alexandrov (Science & Research)

(untitled)
We present is a case of a young 23-year-old woman found in her home in a comatose state, who was taken to the nearest medical center and died there despite the emergency resuscitation measures. The autopsy revealed a characteristic bluish discoloration of the gastric and necrotic changes in the duodenal mucosa. The conducted toxic-chemical studies proved that this was a case of copper sulfate poisoning. This was confirmed by the subsequent inspection at the home of the deceased, where a suicide note was found, written by the deceased, where in addition to the reasons for her decision, she specified the way - intake of copper sulfate.